Teenage pregnancy: a look from a psychosocial perspective (Research, Society and Development, 2022)
Objectives: to analyze psychosocial aspects in pregnant adolescents; describe the feelings and expectations experienced; characterize the psychosocial factors faced. Methodology: exploratory-descriptive study, with a qualitative approach, developed in a primary care unit of the state of Rio de Janeiro, in Nova Iguaçu. The study participants were adolescents who perform prenatal care at the unit. Inclusion criteria: being linked to the unit and aged between 12 and 19 years. Exclusion criteria: (a) those who were not accompanied by a legal guardian to sign the Free and Informed Consent Form; (b) those with a physical or mental condition that prevented their participation; (c) those younger than 12 years old. All ethical and legal requirements proposed by Resolution 466/12 CNS were respected. Data collection was carried out at the institution, using semi-structured interviews and participant observation as instruments. Bardin's content analysis was used for data analysis. Results: the unprepared sexual act is not the only factor responsible for the occurrence of early conception; the deficiency in knowledge, lack of access to information, income, age at menarche and sexarca, family history, education, also contribute significantly to the outcome of this scenario. Conclusion: it is necessary to develop and improve health education programs that give voice to the needs, singularities and expectations of the group in question; that address contexts beyond anatomy and reproductive physiology, especially considering the emotional and sociocultural experiences of society, contributing to the minimization of invisibility and instigating advances in public health.